Comparative Analysis of Visual Field Characteristics and Perceptual Processing in Peripheral Vision Between Virtual Reality and Real World - Dan Bürger; Marc-Kevin Schley; Hannes Loerwald; Stefan Pastel; Kerstin Witte (Human Behavior and Emerging Technologies)
In various domains, virtual reality (VR) has emerged as a valuable tool for simulating specific scenarios and facilitating training within controlled and secure conditions. As peripheral vision plays a crucial role in numerous contexts, it must be duly considered in VR simulations. However, while peripheral vision was examined in VR, comparisons between VR and the real world (RW) are rarely made. Therefore, this study is aimed at comparing RW and VR reaction times (RTs) to peripheral visual stimuli and the field of view (FOV). This comparison is achieved using the peripheral perception-R (PP-R) of the Vienna Test System and a programmed virtual replica. The virtual replica underwent additional testing, revealing good reliability for RTs but only moderate to poor for measurements of the participant’s FOV. The comparison between the two environments indicates slower RTs to peripheral visual stimuli in VR than in RW. This observed discrepancy is consistent with the results of previous studies investigating RTs to foveal stimuli and can be partially explained by the latencies in the hardware and software configurations used. Nevertheless, the observed correlations between the RTs in both conditions suggest comparable visual processing within the peripheral visual field and affirm the decent replication of the real PP-R in VR. Overall, the study’s results support the usage of VR as a tool for practicing and examining specific scenarios, including peripheral vision. The discrepancies revealed in the RTs between VR and RW emphasize the need to continue examining hardware and software components in VR research.